2011
DOI: 10.1039/c1an15067g
|View full text |Cite
|
Sign up to set email alerts
|

Monolith and coating enzymatic microreactors of l-asparaginase: kinetics study by MCE–LIF for potential application in acute lymphoblastic leukemia (ALL) treatment

Abstract: The study of enzyme immobilization using an extracorporeal shunt system is essential to eliminate the side effects of L-asparaginase (L-Asnase; including hepatic toxicity, allergic reaction, pancreatitis, central nervous system toxicity and decreased synthesis of blood clotting factors) when it was applied as an anticancer drug given directly to patients by injection. Thus, the novel monolith and coating enzymatic reactors of L-asparaginase were provided in this assay and a microchip electrophoresis-laser indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 30 publications
(34 reference statements)
0
22
0
Order By: Relevance
“…Low hemolytic WRK variant, WarnG20D, according to its anti-leukemia activity could be good candidates for treatment of leukemia. However, because of the putative cytotoxicity of the peptide for cells other than MNC, it would be interesting to test the efficacy for leukemia therapy of WarnG20D immobilized in an extracorporeal shunt system as proposed by Qiao et al [52] for the anticancer enzyme L-Asnase.…”
Section: Resultsmentioning
confidence: 99%
“…Low hemolytic WRK variant, WarnG20D, according to its anti-leukemia activity could be good candidates for treatment of leukemia. However, because of the putative cytotoxicity of the peptide for cells other than MNC, it would be interesting to test the efficacy for leukemia therapy of WarnG20D immobilized in an extracorporeal shunt system as proposed by Qiao et al [52] for the anticancer enzyme L-Asnase.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, Qiao et al have reported a series of papers on assays for l-asparaginase [161][162][163] which catalyzed the deamidation of Asn and Gln to Asp and Glu, respectively. After enzyme incubation the analytes were derivatized with fluorescein isothiocyanate for microchip electrophoretic separation using LIF-detection.…”
Section: Enzyme Assays Using Microfluidic Devicesmentioning
confidence: 97%
“…After enzyme incubation the analytes were derivatized with fluorescein isothiocyanate for microchip electrophoretic separation using LIF-detection. For offline IMERs the enzyme was immobilized to a glycidyl methacrylate-ethylene dimethacrylate-based monolith [162] or adsorbed to gold nanoparticles that were subsequently immobilized to a (3-mercaptopropyl)-trimethoxysilane-treated capillary [163]. The assays were applied to the determination of the enzyme kinetic data [161][162][163] as well as the deamidation of Asn spiked to human plasma [162].…”
Section: Enzyme Assays Using Microfluidic Devicesmentioning
confidence: 99%
“…It is evident that the drawback of lower concentration LODs is being overcome. Therefore, a growing number of on-chip enzyme assays overtaking macroscale methods even in terms of the concentration LODs can be expected [100].…”
Section: Enzyme Assays In Microchip Formatmentioning
confidence: 99%